China and the World economy: Wavelet spectrum analysis of business cycles - Jitka Poměnková; Jarko Fidrmuc; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2014)
We employ a wavelet spectrum analysis to study globalization and business cycles in China and G7 countries. The co-movement synchronization between G7 countries and China is shown to have undergone frequent and large changes during our sample period. The co-movements for business cycle frequencies are generally different from those for other frequencies, and synchronization with China's business cycle differs as between G7 countries. In recent years Japan, Germany and Italy seem to have the closest synchronization at business-cycle frequency. We find a significant relationship between the time-varying wavelet measure of synchronization and trade only for business-cycle frequencies. The co-movements at longer frequencies are negatively related to trade, so that the overall co-movements and trade tend not to be significantly related.
URN:NBN:fi:bof-201408071930
Keywords: E32; F15; F41; 330; Globalization; business cycles; synchronization; trade; wavelet analysis